Physiological responses of Atlantic cod to climate change indicate that coastal ecotypes may be better adapted to tolerate ocean stressors - Hammar Perry, Diana; Wennhage, Håkan (NATURE PORTFOLIO, 2024)
Healthy ecosystems and species have some degree of resilience to changing conditions, however as the frequency and severity of environmental changes increase, resilience may be diminished or lost. In Sweden, one example of a species with reduced resilience is the Atlantic cod (Gadus morhua). This species has been subjected to overfishing, and with additional pressures such as habitat degradation and changing environmental conditions there has been little to no recovery, despite more than a decade of management actions. Given the historical ecological, economical, and cultural significance of cod, it is important to understand how Atlantic cod respond to global climate change to recover and sustainably manage this species in the future. A multi-stressor experiment was conducted to evaluate physiological responses of juvenile cod exposed to warming, ocean acidification, and freshening, changes expected to occur in their nursery habitat. The response to single drivers showed variable effects related to fish biometrics and increased levels of oxidative stress dependent parameters. Importantly, two separate responses were seen within a single treatment for the multi-stressor and freshening groups. These within-treatment differences were correlated to genotype, with the offshore ecotype having a heightened stress response compared to the coastal ecotype, which may be better adapted to tolerate future changes. These results demonstrate that, while Atlantic cod have some tolerance for future changes, ecotypes respond differently, and cumulative effects of multiple stressors may lead to deleterious effects for this important species.